THU0195 After One Year of Treatment with Biologicals, "Newcomers" Achieve a Comparable Outcome as Patients on Long Lasting Treatment. Characteristics of Austrian Patients with Psoriatic Arthritis and Spondylarthritis; One-year Follow up Data From Bioreg, the Austrian Registry for Biologicals. (9th June 2015) - Rintelen, B.; Herold, M.; Singer, F.; Hitzelhammer, J.; Zwerina, J.; Halder, W.; Eichbauer-Sturm, G.; Puchner, R.; Stetter, M.; Leeb, B.F.
Abstract : Background: BIOREG, the Austrian registry for patients (pts) with chronic rheumatic diseases treated with biologic DMARD's, includes pts with rheumatoid arthritis (RA), spondylarthritis (SPA), psoriatic arthritis (PSA) and other diseases since 2010. Patients on biologic treatment are included irrespective of treatment duration and history. The primary interest of BIOREG is safety; aside disease activity and socioeconomic data are also documented. Objectives: The aim of this evaluation was to figure out eventual differences with respect to safety and disease activity in SPA and PSA pts on long term-treatment or beginners on biologic DMARDs after one year of treatment. Methods: SPA and PSA pts starting their first biologic treatment (NEW) and pts treated with biologics for a longer time (LS) were compared with respect to demographic aspects, disease activity (DA) (BASDAI in SPA; total TJC, total SJC and number of dactylitides (DAC) in PSA). Safety concerns were recorded. If not otherwise indicated median values (first and third quartile) are given. Results: SPA: One-hundred-seventy pts (146 LS, 24 NEW) of a total of 362 SPA pts were included into this evaluation as a full dataset was available. Disease duration amounted to 7.0 years (4.0, 15.0) for LS and 3.0 years (1.0, 8.5) for NEW SPA pts. For LS 75.4% were male, the age was 45.0 years (36.0, 52.0), for NEW pts 79.2% and 40.5 (33.5, 49.5) respectively. LS were on biologic DMARDs since 4.21 years (2.17, 5.91). A slight difference in DA can be observed after 1 year according to the BASDAI in favor of NEW (LS 2.45 (1.23, 3.88) and NEW 1.93 (1.20, 3.10). PSA: One-hundred-four pts (85 LS, 19 NEW) out of 239 PSA pts were included into this evaluation as a full dataset was available. Disease duration amounted to 8.0 years (4.0, 14.0) for LS and 3.0 years (1.0, 10.0) for NEW pts, 60.7% were male, 57.9% respectively, the age was 53.0 years (45.0, 59.0) and 47.0 (39.0, 54.0) respectively. LS were on biologic DMARDs since 3.75 years (1.77, 5.74). No difference in DA can be observed after 1 year according to TJC (LS as well as NEW 0.0 (0.0, 1.0)), to SJC (LS as well as NEW 0.0 (0.0, 0.0)) and to dactylitis (LS in 11.8%, NEW 10.5%). In both groups, 63 adverse events had to be noticed in the LS pats (27%) and 10 in the NEW pats (30%) most likely infections. Conclusions: After 1 year of biologic treatment, all pts achieve a comparable level of disease activity control. Adverse events occur in both groups in around 30% with no difference in LS and NEW. Disclosure of Interest: B. Rintelen Grant/research support from: BIOREG is supported by an unrestricted industrial grant, M. Herold Grant/research support from: BIOREG is supported by an unrestricted industrial grant, F. Singer Grant/research support from: BIOREG is supported by an unrestricted industrial grant, J. Hitzelhammer Grant/research support from: BIOREG is supported by an unrestricted industrial grant, J. Zwerina Grant/research support from: BIOREG is supported by an unrestricted industrial grant, W. Halder Grant/research support from: BIOREG is supported by an unrestricted industrial grant, G. Eichbauer-Sturm Grant/research support from: BIOREG is supported by an unrestricted industrial grant, R. Puchner Grant/research support from: BIOREG is supported by an unrestricted industrial grant, M. Stetter Grant/research support from: BIOREG is supported by an unrestricted industrial grant, B. Leeb Grant/research support from: BIOREG is supported by an unrestricted industrial grant